Sistem Penunjang Keputusan Penerimaan Karyawan Baru di PT. Yudita Teratai Cakti Menggunakan Metode Profile Matching - Lau, Herminus; Faizah, NM; Ginting, Winton (Journal Innovations Computer Science, 2022)
PT. Yudita Teratai Cakti is a company that carries out the hiring process independently or does not use the services of an outsourcing company. In the process of hiring employees, usually PT. Yudita Teratai Cakti uses advertising services in print media such as newspapers and online media such as Facebook and others. In the employee recruitment process at PT. Yudita Teratai Cakti is carried out by the personnel department by selecting and selecting one by one the data of applicants who enter the selection process for prospective employees at the acceptance of new employees at PT. Yudita Teratai Cakti, with the need to apply for a job this system was built, namely carrying out a selection process for prospective employees who applied for work at PT Yudita Teratai Cakti, it is hoped that this system can carry out the selection process using the profile matching calculation method used in this study to be able to provide decision-making information New Employee Recruitment. In order for the implementation of the selection of new employees to meet the demands and expectations of the company, a correlation is needed between the preparation of the test questions and the determined test criteria so that the test results for each new employee show the potential value of each new employee on each of the specified criteria. The decision support system with the profile matching method can assist the role of management or managers in supporting PT. Yudita Teratai Cakti which has objective value with a more effective time.